IMPROVING STUDENTS’ SPEAKING SKILL BY USING THREE STEP INTERVIEW AT LINTASAN IMAJINASI BAHASA MAHASISWA (LIBAM) IAIN PAREPARE - Ramadhan Aras; Magdahalena Magdahalena; Abd Rauf Ibrahim (Inspiring: English Education Journal, 2019)
English as primary and foreign language has become the key to the world. However, it must be found the way how to be mastered it. One of the skills which are very important is speaking skill because it will help people to communicate and interact each other. This research was carried out at LIBAM IAIN Parepare. In this case, the researcher found that some members of LIBAM IAIN Parepare are still a law in speaking especially in front of their friends or other people. To solve the problem, the researcher used three step interview. This technique is one of student center learning which learners help each other and learn. The objective of the research is to know whether three step interview is able or not to improve the speaking skill of members of LIBAM IAIN Parepare. The population was the members of LIBAM IAIN Parepare and the sample of this research was 25 members. The researcher used pre-experimental design in one group was given pre-test, treatment and post-test design, as for the effect of treatment was judged by the difference between the pre-test and post-test. The success of the treatment is determined by comparing pre-test and post-test score. To collect the data, the researcher used tests that are pre-test and post-test. The researcher also gave questionnaire to know the responses of students to three step intervew. The data were analyzed as a percentage, mean score analyzes and the value of the test. The first result of the data analyzed that the students’ achievement on the pre- test was (6,36) and post-test was (7,26) This showed that by using three step interview was a good technique in English learning process at Lintasan Imajinasi Bahasa Mahasiswa (LIBAM) IAIN Parepare. After analyzing the data by using the t- test formula, the result of the t-test value (9,64) is bigger than the t-table value (1,7108).It means that there is a different improvement before and after using three step interview as technique of teaching. The second result of analyzed data that 72% of the students were interested in using three-ste interview, in the other word most of them interested to apply three step interview.